Differences in food consumption according to weight status and physical activity levels among Greek children between 1992/93 and 2006/07. Issue 3 (28th November 2012) - Smpokos, E. A.; Linardakis, M.; Sarri, K.; Papadaki, A.; Theodorou, A. S.; Kafatos, A.
Abstract Background There is a lack of data in Greece on trends in food intake according to weight status and physical activity (PA), despite the high prevalence of obesity. The present study aimed to examine differences in these parameters among first‐grade children from Crete, Greece, over a 15‐year period. Methods Children (aged 5.9–7.6 years) from two representative cross‐sectional studies participated during 1992/93 (n = 245) and 2006/07 (n = 257). Estimated 3‐day food records were used to assess food consumption and energy‐density (ED) [kJ g−1 (kcal g−1)]. Moderate‐to‐vigorous‐PA (MVPA) and cardiorespiratory‐fitness were assessed by questionnaires and the 20‐m shuttle‐run test (20mSRT), respectively. Results In 2006/07, compared to 1992/93, both sexes had a significantly higher intake of dairy products and snacks (P < 0.001), a lower intake of cereals (P < 0.001) and higher cardiorespiratory fitness levels (P < 0.001). Among girls, fruit/vegetable consumption was higher (P < 0.05), although legume intake was lower (P < 0.005). Among overweight/obese (OW/OB) children, ED significantly decreased (P < 0.05) and the mean consumption of fruits/vegetables was higher (P < 0.001). The percentage of OW/OB boys was significantly higher (P < 0.001); however, MVPA was significant higher in this group compared to 1992/93 (P < 0.001). During the two time‐periods, active children in 2006/07 appeared to have a lower ED than active ones in 1992/93 (P < 0.001). Conclusions Several differences in food intake were observed among first‐grade children of Crete between 1992/93 and 2006/07, as characterised by significant increases in the consumption of dairy products and snacks and a decrease in the intake of cereals, among both sexes. Future school‐based interventions in this population should emphasise the need to increase fruit/vegetable, unrefined cereal and legume consumption.